2022
DOI: 10.1177/11206721221076313
|View full text |Cite
|
Sign up to set email alerts
|

New insights in pathogenic mechanism of hydroxychloroquine retinal toxicity through optical coherence tomography angiography analysis

Abstract: Introduction There is only a unique report with a small sample size studying hydroxychloroquine (HCQ) retinal toxicity with swept-source (SS) optical coherence tomography angiography (OCTA). The aim of this study was to quantify OCTA quantitative parameters in patients who underwent HCQ therapy. Methods We conducted a retrospective study. The study included 43 eyes of 22 patients taking HCQ for more than 5 years (high-risk group), 57 eyes of 29 patients taking HCQ for 5 years or less (low-risk group) and 25 ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Some scholars have speculated that the retinal toxicity of hydroxychloroquine may not be mediated by blood vessels. 24 The retinal blood flow changes found in our study may be the joint effect of the disease itself and hydroxychloroquine. Future research could include children with extremely short disease durations to avoid the interference of hydroxychloroquine.…”
Section: Discussionmentioning
confidence: 54%
“…Some scholars have speculated that the retinal toxicity of hydroxychloroquine may not be mediated by blood vessels. 24 The retinal blood flow changes found in our study may be the joint effect of the disease itself and hydroxychloroquine. Future research could include children with extremely short disease durations to avoid the interference of hydroxychloroquine.…”
Section: Discussionmentioning
confidence: 54%
“…Our results showed that DVD demonstrated a negative correlation with HCQ treatment, which was similar to Forte et al.’s study ( 19 ). While some researchers observed an increase of VD in patients who underwent HCQ treatment or no significant differences ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 95%
“…However, Remolí Sargues et al . [ 24 ] found very conflicting results in their retrospective study and suggested that HCQ retinal toxicity is not vascular-mediated.…”
Section: Discussionmentioning
confidence: 99%